Pelatihan Kader Posyandu dalam Pembuatan Biskuit Kaya Protein Ikan di Desa Cileles, Jatinangor, Sumedang - Junianto Junianto; Zahidah Zahidah; Kiki Haetami (Institut Pertanian Bogor, 2021)
The role of mothers is very important in increasing the consumption of fish protein for toddlers and children. Consumption of fish protein is very useful for maintaining health, accelerating growth and development of children, and increasing intelligence. The aim of this program is to provide knowledge and train skills in making biscuits rich in fish protein fortified with nilem fish meat flour to Posyandu women as the target audience in Cileles Village, Jatinangor Subdistrict, Sumedang District. This activity lasts for seven months, from May to December 2020. The methods used training in making fish potein – rich biscuit. Based on the results of the activities that have been carried out, it can be concluded that posyandu caders have been knowledge and skills in making fish protein-rich biscuits fortified with nilem fish meat flour. Organoleptically produced products are preferred by panelis.